The characteristics of fermented purple sweet potato (Ipomoea batatas) and black rice (Oryza sativa) using UV-irradiated Monascus purpureus - ISWIYANTI NOVITA; OEDJIJONO OEDJIJONO; ARI ASNANI (Society for Indonesian Biodiversity, 2021)
Abstract. Novita I, Oedjijono, Asnani A. 2021. The characteristics of fermented purple sweet potato (Ipomoea batatas) and black rice (Oryza sativa) using UV-irradiated Monascus purpureus. Biodiversitas 22: 684-690. This research aimed to produce Monascus fermented product (MFP) with purple sweet potato (Ipomoea batatas (L.) Lam.) and black rice (Oryza sativa L.) using UV-irradiated Monascus purpureus Went and evaluated the characteristic of its antibacterial activity against Salmonella typhi. M. purpureus was irradiated with UV at l254 nm for 0, 2, 3, and 4 min. The solid-state fermentation process was carried out for 7, 14, and 21 days. The pigments were measured at l390 nm for yellow and l500 nm for red. The ethanol extracts of MFP were analyzed for their antibacterial activity against S. typhi using the Kirby–Bauer method. The results showed that the highest yield of MFP was obtained from MFP–black rice (51.88%) that used UV-irradiated M. purpureus for 2 min and fermentation for 21 days. The highest absorbance value of MFP–purple sweet potato was obtained from UV-irradiated M. purpureus for 3 min, whereas the highest absorbance value of MFP–black rice was obtained with UV-irradiated M. purpureus for 2 min. Ethanol extracts of both MFP3–purple sweet potato and MFP2–black rice showed antibacterial activities against S. typhi with minimum inhibitory concentration values of 0.2 and 0.15 g/mL, respectively. Thin-layer chromatography analysis of the ethanol extract from MFP2–black rice revealed the presence of bioactive saponin and flavonoid. These findings suggest that UV-irradiated M. purpureus was able to use both purple sweet potato and black rice substrates to produce MFP with antibacterial activity against S. typhi.